2021
DOI: 10.1002/hep.31641
|View full text |Cite
|
Sign up to set email alerts
|

Ras Homolog Family Member F, Filopodia Associated Promotes Hepatocellular Carcinoma Metastasis by Altering the Metabolic Status of Cancer Cells Through RAB3D

Abstract: Background and Aims The mechanism by which tumor cells resist metabolic stress remains unclear, but many oncogenes are known to regulate this process. Accordingly, metabolic stress is closely associated with tumor metastasis. In this study, gene chip technology showed that Ras homolog family member F, filopodia associated (RHOF), a member of the Rho guanosine triphosphatase family, is an oncogene that is significantly related to hepatocellular carcinoma (HCC) metastasis; however, it has rarely been reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Baik et al found that ZBP1 mediated necroptosis of breast cancer induced by GS [ 21 ]. RHOF also acts as a protector of hepatocellular carcinoma and promotes metabolic reprogramming under glucose deprivation conditions [ 22 ]. However, cancer cells tend to rob nutrition from the human body to adapt to their highly proliferative states.…”
Section: Discussionmentioning
confidence: 99%
“…Baik et al found that ZBP1 mediated necroptosis of breast cancer induced by GS [ 21 ]. RHOF also acts as a protector of hepatocellular carcinoma and promotes metabolic reprogramming under glucose deprivation conditions [ 22 ]. However, cancer cells tend to rob nutrition from the human body to adapt to their highly proliferative states.…”
Section: Discussionmentioning
confidence: 99%
“…RHOF is a member of the Rho GTPase family, an oncogene that plays an important role in tumor cell invasion and migration. High expression of RHOF is closely associated with tumor progression and poor survival of patients [48,49]. Yang et al found that targeting RHOF could improve the sensitivity of pancreatic cells to gemcitabine treatment through the EMT pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the role of exosomes in EMT progression in different types of cancer, including HCC. 69 Chen et al 70 revealed that HCC-derived exosomes promoted HCC progression and recurrence by activating EMT through the MAPK/ERK signaling pathway. Rab27a, a small GTPase, regulates exosome secretion by mediating multivesicular endosome docking at the plasma membrane.…”
Section: Role Of Exosomes In the Formation Of Hcc Microenvironmentmentioning
confidence: 99%